2016
DOI: 10.1016/j.jobcr.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of smoking on the levels of matrix metalloproteinase-8 and periodontal parameters in smoker and nonsmoker patients with chronic periodontitis: A clinicobiochemical study

Abstract: This study suggests that MMP-8 is involved in periodontal destruction associated with smoking. Additionally, smoking exerts disastrous effects on immune response and can affect the pathogenesis of disease; hence, smoking results in increased severity of periodontal destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Results of this study are in partial agreement with the proposed hypotheses as scores of PI and PD ≥4 mm were significantly higher among individuals in group 1 than among individuals in groups 2 and 3. Previous studies 18‐20 have also confirmed that CSs exhibit significantly greater number of sites with plaque accumulation, clinical AL, and PD ≥4 mm compared with NSs. One explanation in this context is that tobacco smoking is associated with increased expression of AGEs and their receptors in gingival tissues, which exacerbate oxidative stress and inflammatory responses 21 .…”
Section: Discussionmentioning
confidence: 68%
“…Results of this study are in partial agreement with the proposed hypotheses as scores of PI and PD ≥4 mm were significantly higher among individuals in group 1 than among individuals in groups 2 and 3. Previous studies 18‐20 have also confirmed that CSs exhibit significantly greater number of sites with plaque accumulation, clinical AL, and PD ≥4 mm compared with NSs. One explanation in this context is that tobacco smoking is associated with increased expression of AGEs and their receptors in gingival tissues, which exacerbate oxidative stress and inflammatory responses 21 .…”
Section: Discussionmentioning
confidence: 68%
“…Levels of matrix metalloproteinase-8 (MMP-8), which is involved in periodontal destructions, are significantly increased in smoking patients. Additionally, immune response is modified and the pathogenesis of the disease is negatively affected [8]. A similar pattern is present in patients affected by type 2 diabetes mellitus suggesting that diabetic-smoker patients have increased periodontal breakdown and are prone to a more severe periodontitis [9].…”
Section: Comprehensive Diagnosismentioning
confidence: 93%
“…Apart from genetic influences, other risk factors such as diabetes, smoking and stress should also be considered, controlled and integrated into the overall treatment plan. The destructive effects of smoking on periodontal tissues have long been recognized, and recent biochemical and genetic studies have clarified direct and indirect pathways of this association [7,8]. Levels of matrix metalloproteinase-8 (MMP-8), which is involved in periodontal destructions, are significantly increased in smoking patients.…”
Section: Comprehensive Diagnosismentioning
confidence: 99%
“…For example, MMP‐8 concentrations in oral fluids have been reported to be either higher, lower, or similar based on smoking status. Smokers had significantly elevated MMP‐8 levels in saliva, higher MMP‐8 protein expression in periodontal tissue, and higher collagenolytic activity when compared with non‐smokers. On the contrary, lower levels of MMP‐8 in oral fluids are reported in smokers compared with non‐smokers .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the established risk factors for periodontal disease and elevated odds for periodontal progression are observed for both involuntary and active smokers . Smoking disturbs the normal host response, and smokers have more progressed periodontal tissue destruction, that is, greater attachment loss, deeper probing depths, more tooth loss, and more alveolar bone loss (ABL) compared with non‐smokers . Smoking causes vasoconstriction, thus less gingival bleeding is observed in patients with periodontitis who smoked .…”
Section: Introductionmentioning
confidence: 99%